Immunological and virological response to initial antiretroviral therapy among older people living with HIV in the Canadian Observational Cohort (CANOC). Issue 8 (1st June 2021) - Zhabokritsky, A; Szadkowski, L; Burchell, AN; Cooper, C; Hogg, RS; Hull, M; Kelly, DV; Klein, M; Loutfy, M; McClean, A; Montaner, J; Walmsley, SL; et al.
Abstract : Objectives: The aim of this study was to assess the adequacy of immunological recovery and virological suppression in response to antiretroviral therapy (ART) in the growing population of older people living with HIV (PLWH), as treatment regimens become more effective and tolerable. Methods: An interprovincial Canadian cohort of treatment‐naïve PLWH who initiated ART after 1 January 2000 was used and age assessed in decades. Longitudinal absolute CD4 count response to treatment was modelled using generalized estimating equations. Cumulative incidence functions and proportional hazards models with a competing risk of death were used to estimate time to: (1) CD4 ≥ 200 cells/µL, (2) CD4 ≥ 500 cells/µL, (3) virological suppression (≤ 50 copies/mL), and (4) virological failure (> 200 copies/mL). Results: In all, 12 489 individuals starting ART between 2000 and 2016 with one or more post‐treatment CD4 count or viral load were included in the analysis. Age > 60 years was associated with lower absolute CD4 recovery (adjusted β = −31 cells/µL) compared with age ≤ 30 years when pre‐treatment CD4 count and other covariates were accounted for. Older age groups were less likely to achieve a CD4 ≥ 500 cells/µL, with the greatest effect in the > 60 group [adjusted hazard ratio (aHR) = 0.69, 95% confidence interval (CI): 0.57–0.84 vs . age ≤ 30). Older age groups were more likely to achieve viral suppression (age > 60, aHR = 1.20, 95% CI: 1.05–1.37) and less likely to have virological failure (age > 60, aHR = 0.46, 95% CI: 0.3–0.71) compared with those aged ≤ 30 years. Conclusions: Older adults have robust virological responses to ART; however, individuals over the age 60 are more likely to experience blunted CD4 recovery.